The study of embedded wing aerodynamic-the ray fish configuration - 396378 Nazri Talib (Skudai : Universiti Teknologi Malaysia, 2004)
Project Paper (Bachelor of Mechanical Engineering (Aeronautical)) - Universiti Teknologi Malaysia, 2004